2009
DOI: 10.1038/nm.1943
|View full text |Cite
|
Sign up to set email alerts
|

Imaging transforming growth factor-β signaling dynamics and therapeutic response in breast cancer bone metastasis

Abstract: Although the transforming growth factor-beta (TGF-beta) pathway has been implicated in breast cancer metastasis, its in vivo dynamics and temporal-spatial involvement in organ-specific metastasis have not been investigated. Here we engineered a xenograft model system with a conditional control of the TGF-beta-SMAD signaling pathway and a dual-luciferase reporter system for tracing both metastatic burden and TGF-beta signaling activity in vivo. Strong TGF-beta signaling in osteolytic bone lesions is suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(175 citation statements)
references
References 32 publications
4
170
0
1
Order By: Relevance
“…46 Moreover, zoledronate displays antiangiogenic activity and can decrease the secretion of immunosuppressive (TGF-b, FGF-b and metalloproteinases) and proinflammatory (IL-1b, IL-6 and IL-8) factors. 42,[47][48][49][50] In a previous clinical trial designed to evaluate phosphoantigen administration in B-cell malignancies, a correlation was observed between the in vivo expansion of Vc9Vd2 T cells and the objective antitumor response. 18 An adoptive transfer immunotherapy assay has also been conducted in metastatic renal cell carcinoma by Kobayashi et al 21 and in lung carcinoma by Nakajima et al 51 These studies found that autologous Vc9Vd2 T cells are well tolerated and induce an antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, zoledronate displays antiangiogenic activity and can decrease the secretion of immunosuppressive (TGF-b, FGF-b and metalloproteinases) and proinflammatory (IL-1b, IL-6 and IL-8) factors. 42,[47][48][49][50] In a previous clinical trial designed to evaluate phosphoantigen administration in B-cell malignancies, a correlation was observed between the in vivo expansion of Vc9Vd2 T cells and the objective antitumor response. 18 An adoptive transfer immunotherapy assay has also been conducted in metastatic renal cell carcinoma by Kobayashi et al 21 and in lung carcinoma by Nakajima et al 51 These studies found that autologous Vc9Vd2 T cells are well tolerated and induce an antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Upon reaching the bone microenvironment, cancer cells activate the differentiation of bone-degrading osteoclasts either directly or indirectly by promoting the increased production of osteoclastogenesis cytokines by osteoblasts [2]. Differentiated osteoclasts dissolve mineralized bone, leading to the release of a large compendium of growth factors and cytokines, such as PDGF, FGF, and IGFs and TGF-β [2][3][4], from the bone matrix, which in turn promote the growth of and continued pro-osteolytic signaling by cancer cells [5]. Notably, communication between cancer cells and bone stromal cells is typically mediated via secreted proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-produced factors such as parathyroid hormone-related protein (PTHrP), interleukin-11 (IL-11), IL-6, and IL-8 stimulate bone resorption to release and activate growth factors housed in the mineralized bone matrix. Bone-derived TGF-b promotes osteolysis by stimulating tumor production of osteolytic factors, and alters the bone microenvironment to further increase osteoclastic bone resorption and inhibit bone formation Korpal et al 2009;Mohammad et al 2009). These tumor-bone interactions result in a feed-forward cycle to promote tumor growth in bone.…”
mentioning
confidence: 99%